Intellectual property protection of folklore: a step towards a more global approach - Radonjanin, Andrea (2016)
Folklore, as a specific part of the traditional heritage, forms one of the constituent elements of the cultural identity of every community. As such, expressions of folklore ought to be preserved and protected from uncontrolled and inappropriate utilisation. The problem of an adequate system of protection of folklore has been discussed over the last few decades, yet, it seems that, up to date, legislative solutions fail to entirely efficiently and comprehensively deal with this issue.